Ausubel’s understanding of concept development - Janković, Aleksandar P (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
This paper presents one of relatively new cognitivistic learning and cognition theories – the theory by American psychologist David Ausubel. We consider this theory to be very usable for teaching beginners or for cognition process. It is of utmost importance that first or elementary concepts concerning natural and social phenomena a pupil aquires need to be accurate, understandable and properly connected in a cause-effect sequence of conceptual systems so that items of knowledge aquired can be stable and usable. For correct understanding of Ausubel’s claims concerning processes and procedures involved in the acquisition of elementary concepts, which is central to this investigation, it is necessary to address problems and questions concerning the following: the process of aquisition or construction of first concepts; how to base verbal learning; how is subsuming achieved, that is connecting of new and previously acquired concepts; what is the relation of this theory with other cognitivistic theories of learning, and, finally, what are critical views or evalutions which can make this theory truly productive in relation to teaching.